Selbstinszenierungspraktiken als Weg zu Stärkenorientierung, Selbstbestimmung und Teilhabe – eine Kollegiale Weiterbildung für multiprofessionelle Akteursgruppen im (inklusiven) Übergang Schule-Beruf - Kundisch, Heike; Kremer, H.-Hugo; Otto, Franziska (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Der Beitrag stellt ein Qualifizierungsformat für (multi)professionelle Bildungsakteur*innen zur entwicklungsförderlichen Nutzung von Selbstinszenierungspraktiken vor. Die Konzeption und Entwicklung des Weiterbildungsformats ist im Rahmen eines Forschungs- und Entwicklungsprojekts für Jugendliche in ausbildungsvorbereitenden Bildungsgängen angesiedelt, die einen besonderen Förderbedarf im Zuge des Übergangs von der Schule in die Berufs- und Arbeitswelt aufweisen. Diese sollen durch offene und kreative Selbstdarstellungs- und Erhebungsformate dabei unterstützt werden, ihre Stärken zu erkennen, zu dokumentieren und sichtbar zu machen, sowie hierüber gleichsam für den Übergang Schule-Beruf gestärkt werden. Wir stellen zunächst den Projektrahmen vor und schärfen in diesem Kontext den Zugang über eine Grundlegung zu Selbstinszenierung sowie deren Potenziale im Kontext der inklusiven Berufsbildung und zur Stärkung der Zielgruppe. Das im Projekt entwickelte Rahmenkonzept bietet eine Orientierung zur standort- respektive bildungsgangbezogenen Anpassung und stellt damit Herausforderungen und einen entsprechenden Qualifizierungsbedarf für Bildungsakteur*innen heraus. Darauf basierend stellen wir die konzeptionellen Grundlagen, die methodische und inhaltliche Ausgestaltung zum Ansatz der ‚Kollegialen Weiterbildung‘ zur entwicklungsförderlichen Nutzung von Selbstinszenierungspraktiken vor und adressieren u. a. das Zusammenspiel von innovativer Entwicklung, Schärfung von Rollen und Kompetenzentwicklung der Bildungsakteur*innen. Abschließend diskutieren wir die konzeptionellen Entwicklungen und den Implementations- und Transferansatz. Abstract The article presents a qualification format for multi-professional actors in the educational context on the developmental use of 'Selbstinszenierungspraktiken' (which means a combination of practices for self-awareness, self-realisation and self-acceptance in a process which we are developing in our project). The concept and development of the further education format is located within the framework of a research and development project for young people with wide-ranging needs in pre-vocational education units at the transition from school to work. They will be supported in recognizing, documenting and showing their strengths through open and creative self-expression and survey formats, as well as being strengthened for the transition from school to work. First, we present the project framework and clarify the approach by a theoretical grounding of ‚Selbstinszenierung‘ (similar to a combination of self-awareness, self-realisation and self-acceptance) as well as its potentials in the context of inclusive vocational education by strengthening the target group. The developed framework provides a basis for the adaptation of the concept to a specific location or educational programme and highlights challenges and qualification needs for actors in the educational context. We present the conceptual basis, the methodological and content-related design of the collegial training approach on the developmental use of 'Selbstinszenierungspraktiken'. We address the interaction of innovative development, clarification of roles and competence development of actors in the educational context. Finally, we discuss the conceptual developments and the implementation and transfer approach.
Keywords: General Medicine

HenDi-Data (data package) v3.1.0 - Ried, Dennis; Capelle, Irmlind; Minetti, Elena; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

HenDi-Data (data package) v3.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

Jahrgangsteams zur Kooperation mit Eltern anregen – eine Aufgabe für Fortbildungen? Evaluationsergebnisse zum Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) - Grüter, Sandra; Gorges, Julia; Lütje-Klose, Birgit; Neumann, Phillip; Wild, Elke (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Für eine gelingende Umsetzung schulischer Inklusion gilt eine professionelle Weiterbildung der Lehrkräfte und des weiteren Schulpersonals als unverzichtbare Voraussetzung, um eine effektive Teamarbeit sowie die Einbindung von Eltern[i] in Erziehungs- und Bildungsprozesse zu gewährleisten. Im Projekt BiFoKi[ii] (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde eine Fortbildungsmaßnahme für inklusive Schulen entwickelt, die sowohl die intrainstitutionelle Kooperation innerhalb der Schule als auch die interinstitutionelle Zusammenarbeit mit den Eltern der Schüler*innen mit und ohne sonderpädagogischen Unterstützungsbedarf adressiert. Die Fortbildung zielt u.a. darauf ab, durch eine im Jahrgangsteam gemeinsam geplante und verantwortete Elternarbeit eine einladende Atmosphäre zu schaffen, Kommunikationswege an diverser werdende Bedarfe der Eltern und der Schüler*innen anzupassen und Eltern stärker in schulische Bildungsprozesse einzubeziehen. Zur Evaluation der Fortbildung wurde eine quasi-experimentelle Studie mit einem Prä-Post-Kontrollgruppendesign realisiert. Längsschnittliche Daten liegen für 55 Lehr- und Fachkräfte vor. Die Ergebnisse der varianzanalytischen Auswertung zeigen, dass sich die Einschätzungen zur Kooperationsbereitschaft der Eltern sowie das selbstberichtete Kooperationsverhalten im Bereich der Erziehungs- und Bildungskooperation in der Interventionsgruppe nach der Teilnahme an der Fortbildung signifikant positiver entwickelt hat als in der Kontrollgruppe. [i] Mit dem Begriff Eltern sind hier alle erziehungs- bzw. sorgeberechtigten Personen gemeint. [ii] Hinweis zur Finanzierung: Das diesem Beitrag zugrunde liegende Vorhaben BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde mit Mitteln des Bundesministeriums für Bildung und Forschung unter dem Förderkennzeichen 01NV1732in der Förderlinie „Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung“ gefördert (Projektleitung: Birgit Lütje-Klose, Elke Wild, Julia Gorges und Phillip Neumann). Abstract To implement inclusive education successfully, it is crucial that teachers and other school staff are trained to cooperate effectively as a team and to involve parents in educational processes. In the project BiFoKi (Bielefeld Training on Cooperation in inclusive), we developed an in-service training for inclusive schools that addresses the intra-institutional cooperation within schools and the inter-institutional cooperation with the parents of students with and without special educational needs. The training aims to prepare grade-level teams to create a welcoming atmosphere, adapt communication ways to the diverse needs of parents and students and to involve parents more strongly in school educational processes. To evaluate the effectiveness of the training, a quasi-experimental study with a pre-post control group design was implemented. Longitudinal data is available for 55 teachers and other professionals. The results indicate that the intervention group demonstrated a more positive development in terms of satisfaction with parents' willingness to cooperate as well as self-reported cooperative behavior in the area of educational cooperation, compared to the control group.
Keywords: General Medicine

The Demand for Voluntary Carbon Dioxide Removal – Experimental Evidence from an Afforestation Project in Germany - Bartels, Lara; Kesternich, Martin; Löschel, Andreas (Land Economics)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Governing autonomies. Imagining responsible AI in the European armament project “Future Combat Air System” - Hälterlein, Jens (The Reality of Autonomous Weapon Systems)

The Stellarium Gornergrat: Astrophysics with your own Data - Gschwind, Stéphane; Hohmann, Sascha; Müller, Andreas; Nordine, Jeffrey; Riesen, Timm-Emanuel (Journal of Physics: Conference Series)
Abstract Remote-controlled telescopes in education provide the opportunity to obtain high quality astronomy images for a broad variety of users. The Stellarium Gornergrat is such a telescope. In addition to pure observation, it offers a user-friendly interface and teaching modules so that astronomical and astrophysical projects can be integrated into everyday school life without any special prior knowledge and without requiring a lot of time. This contribution presents the Stellarium project and a provides an overview of several teaching activities.
Keywords: Computer Science Applications; History; Education

Cross-project empirical and criteria-oriented analysis of pre-service physics teachers’ pedagogical content knowledge Empirisch-kriterienorientierte Analyse des fachdidaktischen Wissens angehender Physiklehrkräfte - Zeller, Jannis; Schiering, Dustin; Kulgemeyer, Christoph; Neumann, Knut; Riese, Josef; Sorge, Stefan (Unterrichtswissenschaft)
Zusammenfassung In den letzten Jahren wurde das Professionswissen (angehender) Lehrkräfte intensiv untersucht. Neben Aussagen zur inneren Struktur liegen auch Ergebnisse über den Zusammenhang zwischen Professionswissen, Performanz in prototypischen Handlungssituationen sowie Unterrichtserfolg vor. In diesen Analysen hat sich gezeigt, dass insbesondere dem fachdidaktischen Wissen eine zentrale Rolle zukommt. Es mangelt bisher jedoch an empirisch fundierten Beschreibungen von Niveaustufen des fachdidaktischen Wissens. Zwar liegen einzelne Vorschläge vor, diese sind jedoch entweder empirisch nicht fundiert oder post hoc generiert, so dass unklar ist, inwieweit die Beschreibung der Ausprägungen auch außerhalb der jeweiligen Projektkontexte anwendbar ist. Der vorliegende Artikel stellt eine projektübergreifende Analyse des fachdidaktischen Wissens mithilfe zweier Ansätze zur Bildung von Niveaustufen vor. Dazu werden Niveaumodelle mit Daten zum fachdidaktischen Wissen aus zwei Projekten ( $$N=427$$ N = 427 und $$N=779$$ N = 779 ) mithilfe des Scale-Anchoring-Verfahrens sowie eines regressionsanalytischen Ansatzes auf Basis eines Modells hierarchischer Komplexität erstellt. Das Scale-Anchoring-Verfahren liefert Niveaubeschreibungen, die sich zwar bezüglich fachlicher und fachdidaktischer Inhalte unterschieden, aber Parallelen bezüglich lernpsychologisch interpretierbarer Operatoren zeigten. Projektübergreifend deuteten die Ergebnisse daraufhin, dass sich das fachdidaktische Wissen in niedrigen Ausprägungen auf reproduktive Aspekte beschränkt, in höheren Ausprägungen aber kreative und evaluierende Elemente hinzukommen. Das Modell hierarchischer Komplexität zeigte sich nur für einen der Datensätze als geeignet, um ein Niveaumodell abzuleiten und konnte daher für projektübergreifende Analysen nicht weiter genutzt werden. Nichtsdestotrotz lieferte die projektübergreifende Analyse mithilfe des Scale-Anchoring-Verfahrens kontextunabhängige Beschreibungen von Ausprägungen des fachdidaktischen Wissens und ermöglicht so erste Schritte in Richtung eines empirisch fundierten, inhaltlich reichhaltigen Assessments, welches über eine Einordnung mittels eines Scores hinaus geht.
Keywords: Education

HenDi-Data (data package) v4.0.0 - Ried, Dennis; Minetti, Elena; Capelle, Irmlind; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

Jahrgangsteams zur Kooperation mit Eltern anregen – eine Aufgabe für Fortbildungen? Evaluationsergebnisse zum Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) - Grüter, Sandra; Gorges, Julia; Lütje-Klose, Birgit; Neumann, Phillip; Wild, Elke (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Für eine gelingende Umsetzung schulischer Inklusion gilt eine professionelle Weiterbildung der Lehrkräfte und des weiteren Schulpersonals als unverzichtbare Voraussetzung, um eine effektive Teamarbeit sowie die Einbindung von Eltern [i] in Erziehungs- und Bildungsprozesse zu gewährleisten. Im Projekt BiFoKi [ii] (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde eine Fortbildungsmaßnahme für inklusive Schulen entwickelt, die sowohl die intrainstitutionelle Kooperation innerhalb der Schule als auch die interinstitutionelle Zusammenarbeit mit den Eltern der Schüler*innen mit und ohne sonderpädagogischen Unterstützungsbedarf adressiert. Die Fortbildung zielt u.a. darauf ab, durch eine im Jahrgangsteam gemeinsam geplante und verantwortete Elternarbeit eine einladende Atmosphäre zu schaffen, Kommunikationswege an diverser werdende Bedarfe der Eltern und der Schüler*innen anzupassen und Eltern stärker in schulische Bildungsprozesse einzubeziehen. Zur Evaluation der Fortbildung wurde eine quasi-experimentelle Studie mit einem Prä-Post-Kontrollgruppendesign realisiert. Längsschnittliche Daten liegen für 55 Lehr- und Fachkräfte vor. Die Ergebnisse der varianzanalytischen Auswertung zeigen, dass sich die Einschätzungen zur Kooperationsbereitschaft der Eltern sowie das selbstberichtete Kooperationsverhalten im Bereich der Erziehungs- und Bildungskooperation in der Interventionsgruppe nach der Teilnahme an der Fortbildung signifikant positiver entwickelt hat als in der Kontrollgruppe. [i] Mit dem Begriff Eltern sind hier alle erziehungs- bzw. sorgeberechtigten Personen gemeint. [ii] Hinweis zur Finanzierung: Das diesem Beitrag zugrunde liegende Vorhaben BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde mit Mitteln des Bundesministeriums für Bildung und Forschung unter dem Förderkennzeichen 01NV1732in der Förderlinie „Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung“ gefördert (Projektleitung: Birgit Lütje-Klose, Elke Wild, Julia Gorges und Phillip Neumann).
Keywords: Inklusion; Kooperation; Eltern; Sekundarstufe 1; Evaluation; Integration; Schulentwicklung; Elternkooperation

Concept and Implementation of a Student Design Project for the Development of Sustainable Products - Wurst, Johanna; Rosemann, Daniel; Mozgova, Iryna; Lachmayer, Roland

Evaluation of self-built low-budget particle sensors (Study Project) - Al Mamoun, Mohamed; Neukötter, Moritz

IngridKG: A FAIR Knowledge Graph of Graffiti - Sherif, Mohamed Ahmed; da Silva, Ana Alexandra Morim; Pestryakova, Svetlana; Ahmed, Abdullah Fathi; Niemann, Sven; Ngomo, Axel-Cyrille Ngonga (Scientific Data)
Abstract Graffiti is an urban phenomenon that is increasingly attracting the interest of the sciences. To the best of our knowledge, no suitable data corpora are available for systematic research until now. The Information System Graffiti in Germany project ( Ingrid ) closes this gap by dealing with graffiti image collections that have been made available to the project for public use. Within Ingrid , the graffiti images are collected, digitized and annotated. With this work, we aim to support the rapid access to a comprehensive data source on Ingrid targeted especially by researchers. In particular, we present Ingrid KG, an RDF knowledge graph of annotated graffiti, abides by the Linked Data and FAIR principles. We weekly update Ingrid KG by augmenting the new annotated graffiti to our knowledge graph. Our generation pipeline applies RDF data conversion, link discovery and data fusion approaches to the original data. The current version of Ingrid KG contains 460,640,154 triples and is linked to 3 other knowledge graphs by over 200,000 links. In our use case studies, we demonstrate the usefulness of our knowledge graph for different applications.
Keywords: Library and Information Sciences; Statistics; Probability and Uncertainty; Computer Science Applications; Education; Information Systems; Statistics and Probability

IngridKG: A FAIR Knowledge Graph of Graffiti - Sherif, Mohamed; Morim da Silva, Ana Alexandra; Pestryakova, Svetlana; Ahmed, Abdullah Fathi Ahmed; Niemann, Sven; Ngonga Ngomo, Axel-Cyrille
Graffiti is an urban phenomenon that is increasingly attracting the interest of the sciences. To the best of our knowledge, no suitable data corpora are available for systematic research until now. The Information System Graffiti in Germany project (Ingrid) closes this gap by dealing with graffiti image collections that have been made available to the project for public use. Within Ingrid, the graffiti images are collected, digitized and annotated. With this work, we aim to support the rapid access to a comprehensive data source on Ingrid targeted especially by researchers. In particular, we present IngridKG, an RDF knowledge graph of annotated graffiti, abides by the Linked Data and FAIR principles. We weekly update IngridKG by augmenting the new annotated graffiti to our knowledge graph. Our generation pipeline applies RDF data conversion, link discovery and data fusion approaches to the original data. The current version of IngridKG contains 460,640,154 triples and is linked to 3 other knowledge graphs by over 200,000 links. In our use case studies, we demonstrate the usefulness of our knowledge graph for different applications.

Lessons Learned from the Introduction of Systems Engineering - Wilke, Daria; Grothe, Robin; Bretz, Lukas; Anacker, Harald; Dumitrescu, Roman (Systems)
The introduction of Systems Engineering is an approach for dealing with the increasing complexity of products and their associated product development. Several introduction strategies are available in the literature; nevertheless, the introduction of Systems Engineering into practice still poses a great challenge to companies. Many companies have already gained experience in the introduction of Systems Engineering. Therefore, as part of the SE4OWL research project, the need to conduct a study including expert interviews and to collect the experiences of experts was identified. A total of 78 hypotheses were identified from 13 expert interviews concerning the lessons learned. Using exclusion criteria, 52 hypotheses were validated in a subsequent quantitative survey with 112 participants. Of these 52 hypotheses, 40 could be confirmed based on the survey results. Only four hypotheses were rejected, and eight could neither be confirmed nor rejected. Through this research, guidance is provided to companies to leverage best practices for the introduction of their own Systems Engineering and to avoid the poor practices of other companies.
Keywords: Information Systems and Management; Computer Networks and Communications; Modeling and Simulation; Control and Systems Engineering; Software

Venture Client Model: A systematic Literature Review - Haarmann, Lennard; Machon, Fabian; Rabe, Martin; Asmar, Laban; Dumitrescu, Roman (European Conference on Innovation and Entrepreneurship)
Established companies are increasingly opening their innovation systems to stay ahead of the competition. In this context, collaboration with innovative and agile start-ups are gaining continuously more importance. In the past established companies often used common corporate venturing methods such as incubators, accelerators, or corporate venture capital for collaboration. Compared to these methods the venture client model is relatively new and was invented by BMW employees in 2014. Using the venture client model, established companies become early clients of the start-ups even it is still a venture to do so. Together they carry out a pilot project to develop a proof of concept and validate it under real conditions. If successful, they enter a long-term collaboration to integrate the start-up’s solution into products, processes, or business models of the established company. The aim of this paper is to sum up the current literature and set a foundation for future research on this topic. Therefore, we conduct a systematic literature review. As a result, we provide a definition of the venture client model, describe characteristics, present advantages from the perspective of established companies and start-ups. In addition, we summarize the state of research regarding strategy, process, and organizational structure and for the venture client model. In terms of strategy, future research should elaborate defining elements of a strategy as well as ways to integrate the venture client model into the corporate innovation-ecosystem. Focusing on the process additional research is needed on a venture client reference process and its integration into the corporate’s core processes. Referring to the organizational structure a reference architecture for a venture client unit as well as its positioning within the organization (e.g., innovation management or corporate strategy) should be further investigated.

Evidence-based practices in teaching - Rybska, Eliza; Dudziak, Renata; Pollmeier, Pascal (Problemy Wczesnej Edukacji)
This article presents the results of the implementation of the Erasmus Plus project (KA203 financed by the European Union, contract number 2019-1-NL01-KA203-060339) Research in Teacher Education (RiTE). The aim of the project was to promote and facilitate pre-service teachers to create and undertake evidence-based practices in teaching science, technology, engineering, and mathematics (STEM). In the RiTE project, pre-service teachers were encouraged to use evidence from educational and scientific research and to experiment and introduce didactic innovations in teaching and learning processes. Although it has its justification in the tradition of thinking about science, evidence-based practice is not yet consciously applied in school practice. In the article, we present both the theoretical framework for such practices, and the results of qualitative research – an analysis of interviews conducted with students, future teachers, and novice teachers involved in the project. The presented results show changes in the context of an understanding of evidence and what evidence-based practices are in the teaching process and the vision of such teaching presented by the respondents.

Model-based Systems Engineering using Security Design Patterns in the Context of ISO/SAE 21434 - Japs, Sergej; Faheem, Faizan; Anacker, Harald; Husung, Stephan; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The development of modern vehicles is complex, especially regarding compliance with security and safety. ISO/SAE 21434 considers security and safety along the entire product life cycle. According to the standard, a system architecture, a risk analysis, and the application of countermeasures are carried out in the early system design. Design patterns are solutions to known design problems. Security Design Patterns (SDP) describe countermeasures and are used to reduce risk. After our literature review, we did not find a suitable approach that presents SDPs that would be applicable in early system design. In this paper, we present 10 SDPs for early system design, which we evaluated during an 11-week student project with 28 teams. We present the results of the quantitative analysis and the evaluation of the feedback.

Agentenbasierte Modellierung und Simulation im Pandemiemanagement - Hälterlein, Jens (TATuP - Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Mathematical models and computer simulations play a crucial role in the context of the COVID-19 crisis for knowledge about the possible course of the pandemic and for appropriate policy decisions. The paper presents results from an ethnographic study of a government-funded R & D project dealing with agent-based modeling and simulation (ABMS) in the context of pandemic management. Based on the assumption that the use of computer simulations in pandemic management is not only a means to an end for political or epidemiological goals but also plays a significant role in determining which goals and strategies appear politically legitimate, the paper reconstructs how insights into the pandemic are generated in ABMS and specifically in the researched project and made accessible for decision-making.
Keywords: General Medicine

Umgang mit Evidenzen angehender Lehrkräfte in den Naturwissenschaften - Epistemologie in der Lehrkräfteausbildung - Pollmeier, Pascal
Eine Forderung nach evidenzbasierter Praxis (EBP) im Bildungswesen kann sowohl vor dem Hintergrund der Bedeutung wissenschaftlicher Evidenzen innerhalb gesellschaftlicher Diskurse als auch der Evidenzbasierung in anderen Bereichen formuliert werden. Der Umgang mit und die Bewertung von Evidenzen stellen somit vor dem Hintergrund epistemologischer Überzeugungen relevante Aufgaben für den Chemieunterricht dar. Dabei ist unklar, inwiefern (angehende) Lehrkräfte über Kompetenzen in EBP verfügen. Bestehende Studien weisen auf einen Bedarf der fachdidaktischen Analyse und Förderung von Kompetenzen in EBP bei angehenden Lehrkräften hin.Im Rahmen dieser Dissertation wurde die Domänenspezifität der Kompetenzen in EBP sowie deren Förderung in einem fachdidaktischen Kontext untersucht. Dabei wurde ein weiterer Schwerpunkt auf den Umgang mit anomalen Beobachtungen im Sinne widersprüchlicher Evidenzen gelegt. Innerhalb von drei Teilstudien wurden unterschiedliche methodische Zugänge zur Kompetenz in EBP auf Grundlage epistemologischer Überzeugungen gewählt.Die Ergebnisse weisen auf einen Förderbedarf der Kompetenz in EBP für angehende Lehrkräfte aller Unterrichtsfächer hin. Eine entwickelte Intervention für angehende Chemielehrkräfte weist eine Wirksamkeit zur Förderung von Kompetenzen in EBP auf. Im Rahmen einer Modellierungsstudie kann der Einfluss von Fachwissen sowie Indizien für einen Einfluss epistemologischer Überzeugungen auf den Umgang mit anomalen Beobachtungen gezeigt werden.
Keywords: Epistemologie; Evidenzen; evidence-based practice

Mosaic Tiles: Comparative Theological Hermeneutics and Christian-Jewish Dialogue About the Land - Ackermann, Domenik (CrossCurrents)
Keywords: General Engineering

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19. The Teacher-Training-Platform on the SAFE Project Website - Schneider, Jennifer Nicole

Green-4-Future – Project Insights to its best! In: Training and Cooperation Activity (TCA) “Green Erasmus: pathways to sustainable projects and institutions” - Schneider, Jennifer Nicole

STEMinAction- Final Project Meeting – Unlocking Long-Term Sustainability: Harnessing Open Educational Resources (OER) Beyond Project Lifetimes - Schneider, Jennifer Nicole

Multiobjective Optimization of Non-Smooth PDE-Constrained Problems - Bernreuther, Marco; Dellnitz, Michael; Gebken, Bennet; Müller, Georg; Peitz, Sebastian; Sonntag, Konstantin; Volkwein, Stefan (arXiv:2308.01113)
Multiobjective optimization plays an increasingly important role in modern applications, where several criteria are often of equal importance. The task in multiobjective optimization and multiobjective optimal control is therefore to compute the set of optimal compromises (the Pareto set) between the conflicting objectives. The advances in algorithms and the increasing interest in Pareto-optimal solutions have led to a wide range of new applications related to optimal and feedback control - potentially with non-smoothness both on the level of the objectives or in the system dynamics. This results in new challenges such as dealing with expensive models (e.g., governed by partial differential equations (PDEs)) and developing dedicated algorithms handling the non-smoothness. Since in contrast to single-objective optimization, the Pareto set generally consists of an infinite number of solutions, the computational effort can quickly become challenging, which is particularly problematic when the objectives are costly to evaluate or when a solution has to be presented very quickly. This article gives an overview of recent developments in the field of multiobjective optimization of non-smooth PDE-constrained problems. In particular we report on the advances achieved within Project 2 "Multiobjective Optimization of Non-Smooth PDE-Constrained Problems - Switches, State Constraints and Model Order Reduction" of the DFG Priority Programm 1962 "Non-smooth and Complementarity-based Distributed Parameter Systems: Simulation and Hierarchical Optimization".

Approach for a Safety Element out of Context for an Actuator Circuit Control Module - Noun, H.; Mozgova, Iryna; Abdelfattah, M.; Zeller, G.; Rajesh, G.; Lachmayer, R. (International Journal of Industrial and Manufacturing Engineering)
Several modules in automotive are usually modified and adapted for various project-specific applications. Due to a standardized safety concept a high reusability is accessible. A safety element out of context (SEooC) according to ISO 26262 can be a suitable approach. Based on the same safety concept and analysis, common modules can reach high reusability. For developing according to a module out of context, an appropriate and detailed development approach is required. This paper shows how to deduce this development processes for platform modules. Therefore, the detailed approach of the SEooC is derived. The aim is to create a detailed workflow for all phases of the development and integration of any kind of system modules. As an application example, an automotive project for an actuator control module is considered.

HenDi-Data (data package) v2.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

HenDi-Data (data package) v1.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

Designing digital actor engagement platforms for local high streets: an action design research study - Bartelheimer, Christian; zur Heiden, Philipp; Berendes, Carsten Ingo; Beverungen, Daniel (European Journal of Information Systems)
High streets across Europe continue to lose consumers to online retail, leading to business closures and the decline of city centres, impairing cities’ overall liveability. To counter this vicious cycle, our study presents smartmarket2, the first instantiation of a digital actor engagement platform designed specifically for high streets. smartmarket2 enables hybrid online-offline customer journeys by connecting consumers to stores and other high street service providers. In an action design research (ADR) project, we design, implement and evaluate smartmarket2, involving 150 high street operators and 2,300 citizens in three cycles of building, intervention and evaluation. We derive four design principles that contribute prescriptive knowledge on the design of digital actor engagement platforms. Our results reveal that such a platform is able to increase engagement, but that it is subject to actors’ engagement dispositions.
Keywords: Digital platform; action design research; design principles; actor engagement; engagement platform; location-based advertising

A new strategic approach for R&D project portfolio selection using efficiency-uncertainty maps - Namazi, Mehdi; Tavana, Madjid; Mohammadi, Emran; Bonyadi Naeini, Ali (Benchmarking: An International Journal)
Purpose New business practices and the globalization of markets force firms to take innovation as the fundamental pillar of their competitive strategy. Research and Development (R&D) plays a vital role in innovation. As technology advances and product life cycles become shorter, firms rely on R&D as a strategy to invigorate innovation. R&D project portfolio selection is a complex and challenging task. Despite the management's efforts to implement the best project portfolio selection practices, many projects continue to fail or miss their target. The problem is that selecting R&D projects requires a deep understanding of strategic vision and technical capabilities. However, many decision-makers lack technological insight or strategic vision. This article aims to provide a method to capitalize on the expertise of R&D professionals to assist managers in making informed and effective decisions. It also provides a framework for aligning the portfolio of R&D projects with the organizational vision and mission. Design/methodology/approach This article proposes a new strategic approach for R&D project portfolio selection using efficiency-uncertainty maps. Findings The proposed strategy plane helps decision-makers align R&D project portfolios with their strategies to combine a strategic view and numerical analysis in this research. The proposed strategy plane consists of four areas: Exploitation Zone, Challenge Zone, Desperation Zone and Discretion Zone. Mapping the project into this strategic plane would help decision-makers align their project portfolio according to the corporate perspectives. Originality/value The new approach combines the efficiency and uncertainty dimensions in portfolio selection into an integrated framework that: (i) provides a complete representation of the stochastic decision-making processes, (ii) models the endogenous uncertainty inherent in the project selection process and (iii) proposes a computationally practical and visually unique solution procedure for classifying desirable and undesirable R&D projects.
Keywords: Business and International Management; Strategy and Management

A PLACE FOR A DATA SCIENCE PROJECT IN SCHOOL: BETWEEN STATISTICS AND EPISTEMIC PROGRAMMING - PODWORNY, SUSANNE; Hüsing, Sven; SCHULTE, CARSTEN (STATISTICS EDUCATION RESEARCH JOURNAL)
Aspects of data science surround us in many contexts, for example regarding climate change, air pollution, and other environmental issues. To open the “data-science-black-box” for lower secondary school students we developed a data science project focussing on the analysis of self-collected environmental data. We embed this project in computer science education, which enables us to use a new knowledge-based programming approach for the data analysis within Jupyter Notebooks and the programming language Python. In this paper, we evaluate the second cycle of this project which took place in a ninth-grade computer science class. In particular, we present how the students coped with the professional tool of Jupyter Notebooks for doing statistical investigations and which insights they gained.
Keywords: Education; Statistics and Probability

Proaktives Management von Anforderungsänderungen in der Entwicklung komplexer technischer Systeme - Oleff, Christian
Anforderungsänderungen sind ein wesentlicher Grund für Ineffizienzen und Projektfehlschläge in der Entwicklung komplexer technischer Systeme. Proaktives Management von Anforderungsänderungen hat das Potenzial, den Umgang mit Anforderungsänderungen effizienter zu gestalten. Dafür ist ein systematischer Ansatz erforderlich, der eine ganzheitliche Bewertung und Handhabung des Änderungsrisikos im industriellen Entwicklungskontext ermöglicht. Im Rahmen dieser Dissertation wird mit der ProMaRC-Methodik ein neuartiger Ansatz für das proaktive Management von Anforderungsänderungen vorgestellt. Die Methodik wurde in enger Zusammenarbeit mit Industrieanwender:innen aus der Automobilindustrie entwickelt und anhand von fünf Fallstudien validiert. Mittels automatisierter Abhängigkeitsanalyse auf Grundlage künstlicher Intelligenz wird der Anwendungsaufwand gegenüber bestehenden Ansätzen reduziert. Die teilautomatisierte Bewertung und Handhabung der Änderungswahrscheinlichkeit und -auswirkung erfolgt anhand eines modifizierten PageRank-Algorithmus und umfasst erstmalig alle für die Risikoanalyse relevanten Einflussfaktoren. Die Validierung belegt, dass durch die ProMaRC-Methodik eine überzeugende Kombination aus praxistauglichem Anwendungsaufwand und Vollständigkeit der Analyse erzielt wird. Damit erschließt diese Dissertation das bisher kaum beachtete Forschungsfeld des proaktiven Managements von Anforderungsänderungen und fördert eine effizientere Produktentwicklung.

The Scale4Edge RISC-V Ecosystem - Ecker, Wolfgang; Adelt, Peer; Müller, Wolfgang; Heckmann, Reinhold; Krstic, Milos; Herdt, Vladimir; Drechsler, Rolf; Angst, Gerhard; Wimmer, Ralf; Mauderer, Andreas; Stahl, Rafael; Emrich, Karsten; et al. (In Proceedings of the Design Automation and Test Conference and Exhibition (DATE 2022))
This paper introduces the project Scale4Edge. The project is focused on enabling an effective RISC-V ecosystem for optimization of edge applications. We describe the basic components of this ecosystem and introduce the envisioned demonstrators, which will be used in their evaluation.

Who has the future in mind? Gender, time perspectives, and pro-environmental behaviour - Hoffmann, Christin; Hoppe, Julia Amelie; Ziemann, Niklas (Environmental Research Letters)
Abstract An individual’s relation to time may be an important driver of pro-environmental behaviour. We studied whether young individual’s gender and time-orientation are associated with pro-environmental behaviour. In a controlled laboratory environment with students in Germany, participants earned money by performing a real-effort task and were then offered the opportunity to invest their money into an environmental project that supports climate protection. Afterwards, we controlled for their time-orientation. In this consequential behavioural setting, we find that males who scored higher on future-negative orientation showed significantly more pro-environmental behaviour compared to females who scored higher on future-negative orientation and males who scored lower on future-negative orientation. Interestingly, our results are completely reversed when it comes to past-positive orientation. These findings have practical implications regarding the most appropriate way to address individuals in order to achieve more pro-environmental behaviour.
Keywords: Public Health; Environmental and Occupational Health; General Environmental Science; Renewable Energy; Sustainability and the Environment

Performance Management Approach for Digital Platforms in B2B Markets - Özcan, Leon; Kirchberg, Lisa; Koldewey, Christian; Dumitrescu, Roman (The Role of Innovation: Past, Present, Future)
Digital platforms have already led to disruptions in multiple B2C markets and are becoming increasingly dominant in B2B markets. As a result, more and more companies are trying to participate in the platform economy. However, the successful development and operation of a digital platform is associated with significant challenges, which leads to 85% of all platforms failing. A core challenge is the dynamic nature of the platform economy, with varying strategic objectives at different stages in the platform lifecycle. Platform operators must continuously monitor platform progress and adjust their strategy. Utilizing action research in the real-world platform project AI Marketplace, we developed a lifecycle-oriented performance management approach for digital platforms in B2B markets. It enables platform operators to reflect on their position in the platform lifecycle, derive relevant strategic objectives, and monitor them with suitable key performance indicators. Hence, allowing them to secure the long-term success of their platform business.
Keywords: Digital Platform; Two-Sided Market; Multi-Sided Market; Platform Lifecycle; Platform Monitoring; Performance Management

Comparing Student high and low Reading Performance with Differentiated Digital Reading Materials - Paleczek, Lisa; Ender, Daniela; Kogler, Andrea; Seifert, Susanne (European Conference on e-Learning)
The present study investigates eight Grade-4 classes (9- to 12-year-olds, 52.1% girls) who worked on at least 10 lessons using project RegioDiff material. The study focuses on one of these lessons (including nine text passages and corresponding tasks) and on students with low (19 students, percentile <15) and high reading skills (29 students, percentile > 70). While students were working with the material, screencasts were recorded (30h). The construct “task performance” (processing time, response accuracy, and task engagement) was then analysed using the screencasts.
The analysis revealed that the two groups differed significantly in the processing time of two tasks, but not in the total time spent on all nine tasks. Significant differences were revealed also for general task engagement. Task engagement was highly correlated with processing time. Participants with higher reading skills spent more time on the tasks and were more engaged than participants with lower reading skills. However, we did not find any differences in terms of answer accuracy. This indicates that task difficulty and student reading skills were well matched.
The study also shows how tasks may be adapted or augmented in order to match the learning environment more closely to student learning needs.

Responsibility Assignment in Systems Engineering - Gräßler, Iris; Thiele, Henrik; Grewe, Benedikt; Hieb, Michael (Proceedings of the Design Society)
Abstract Increasing system complexity can be controlled by using systems engineering processes. INCOSE defines processes with inputs and outputs (artifacts) for this purpose. Specific SE roles are used to organize the tasks of the processes within the company. In this work, the responsibilities for artifacts are evaluated by means of the RACI scheme and examined by a cluster analysis and discussed for a SE transformation project with a German automotive OEM. As a result of the study, the optimal composition for systems engineering teams is identified and the systems engineering roles are prioritized.
Keywords: systems engineering (SE); project management; model-based systems engineering (MBSE)

Supporting Geometry Learning Digitally-an Interdisciplinary Project to Foster Spatial Competences and Individual Learning Paths by Using Adaptable Algorithmic Feedback Capabilities - Winkelnkemper, Felix; Huhmann, Tobias; Bechinie, Dominik; Eilerts, Katja; Lenke, Michael; Schulte, Carsten (Society for Information Technology & Teacher Education International Conference)
Keywords: ⛔ No DOI found

How to enable pre-service teachers to design technological teaching and learning inclusively? – On the nature and consideration of basic needs in teacher training - Schröer, Franz; Tenberge, Claudia (PATT39 - PATT on the Edge Technology, Innovation and Education)
Theoretical approaches to the transformation towards an inclusive educational system in Germany mostly agree on the involvement of developmental tasks in subject related research (Hinz, 2011). The common understanding of inclusion as a process geared towards equal participation of all children (Booth, 2012) requires a reflexive questioning of established values, attitudes and practices in order to develop inclusive subject related research, teacher training and teaching and learning (Pech & Schomaker, 2013). Among other things, this results in consequences for the design of pre- service teacher training. To a large extent, teacher education is driven by the promotion of central competencies, interests and self-efficacy (Baumert & Kunter, 2011). It aims towards the development and realisation of inclusive interdisciplinary science and social studies (‘Sachunterricht’) in primary education (Moser, 2018). In conjunction with largely acknowledged constructivist approaches to teaching and learning (Möller, 2001), the development of personality, the consideration of basic needs (Deci & Ryan, 1993) and promotion of individual potentials are repeatedly fundamentally represented in subject related and pedagogical considerations (Feuser, 1989; GDSU, 2013). Therefore, the aforementioned constructivist approach is connected to several certain key paradigms for teaching and learning processes (e.g., Vygotskij, 1978; Posner et al., 1982; van de Pol et al., 2010). In this regard, the nature of primary school students’ basic needs have empirically not been sufficiently studied yet. Theoretical frameworks from motivational psychology (Deci & Ryan, 1993) do not explicitly address how individual needs differ and how the diversity of needs can be included in joint-learning, multi-perspective technology education classes. The research project the present paper is part of aims to develop a research-based concept for the professionalisation of pre-service teachers in a seminar course. Therefore, the promotion of the pre- service teachers’ interests and self-efficacy expectations have been assessed in a pre-post research design with a control group visiting another course not related to technology education and inclusion. The present paper describes and discusses first results of the project and will give an outlook on subsequent developmental tasks.
Keywords: Inclusion; basic needs; pre-service teacher training; interest; self-efficacy

Computational Essays as an Approach for Reproducible Data Analysis in lower Secondary School - Hüsing, Sven; Podworny, Susanne (Proceedings of the IASE 2021 Satellite Conference)
Data Science has become an increasingly important aspect of our everyday lives as we gain a lot of different insights from data analyses, for example in the context of environmental issues. In order to make the process of data analyses comprehensible for lower secondary school students, we developed a data analysis project for computer science classes, focusing on gaining insights from environmental data by using the concept of epistemic programming. In this article, we report on the second implementation of this project, which was conducted in a ninth-grade computer science class. Concretely, we want to examine, how far the students were able to create computational essays to conduct reproducible data analyses on their own. In this regard, the computational essays created with the help of the professional tool Jupyter Notebooks will be examined in terms of aspects of reproducibility.

Situational Development of Low-Code Applications in Manufacturing Companies - Kirchhoff, Jonas; Weidmann, Nils; Sauer, Stefan; Engels, Gregor (Proceedings of the 25th International Conference on Model Driven Engineering Languages and Systems: Companion Proceedings)
Companies show an increasing interest in low-code development platforms to facilitate application development by domain experts without sophisticated software development knowledge. Thus, companies aim for a more efficient development of more effective applications since domain experts as so-called citizen developers are no longer limited by the availability and domain knowledge of trained software developers. Nevertheless, efficiency and effectiveness of application development is traditionally also largely influenced by the use of a suitable software development method. Domain experts are, however, not trained in software development methods. This introduces a risk of domain experts creating unusable applications or exceeding the designated time frame of a project (or both). In this paper, we therefore propose an initial version of a situational software development method which supports domain experts in manufacturing companies during the low-code development of applications. The method can be tailored based on situational factors, considering application requirements, features of the used low-code development platform, and characteristics of the development team. We also present feedback corroborating the usefulness of our method and future extension points based on expert interviews.

Automated Requirement Dependency Analysis for Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Hieb, Michael; Preuß, Daniel (Proceedings of the Design Society)
Abstract Requirements changes are a leading cause for project failures. Due to propagation effects, change management requires dependency analysis. Existing approaches have shortcomings regarding ability to process large requirement sets, availability of required data, differentiation of propagation behavior and consideration of higher order dependencies. This paper introduces a new method for advanced requirement dependency analysis based on machine learning. Evaluation proves applicability and high performance by means of a case example, 4 development projects and 3 workshops with industry experts.

Innovative Online Measurement and Modelling Approach for Property-Controlled Flow Forming Processes - Kersting, Lukas; Arian, Bahman; Vasquez, Julian Rozo; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (Key Engineering Materials)
The production of complex multi-functional, high-strength parts is becoming increasingly important in the industry. Especially with small batch size, the incremental flow forming processes can be advantageous. The production of parts with complex geometry and locally graded material properties currently depicts a great challenge in the flow forming process. At this point, the usage of closed-loop control for the shape and properties could be a feasible new solution. The overall aim in this project is to establish an intelligent closed-loop control system for the wall thickness as well as the α’-martensite content of AISI 304L-workpieces in a flow forming process. To reach this goal, a novel sensor concept for online measurements of the wall thickness reduction and the martensite content during forming process is proposed. It includes the setup of a modified flow forming machine and the integration of the sensor system in the machine control. Additionally, a simulation model for the flow forming process is presented which describes the forming process with regard to the plastic workpiece deformation, the induced α’-martensite fraction, and the sensor behavior. This model was used for designing a closed-loop process control of the wall thickness reduction that was subsequently realized at the real plant including online measured feedback from the sensor system.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Knowledge Base Enhanced & User-centric Dialogue Design for OTF Computing - Ahmed, Mobeen
This thesis aims to provide a bidirectional chatbot solution for the requirement engineering process. The Sonderforschungsbereich (SFB) 901 intends to provide the composition of software service On-the-Fly (OTF). The sub-project (B1) of the SFB 901 project deals with the parameters of service configuration. OTF Computing aims to eradicate the dependency on the requirement engineers for the software development process. However, there is no existing bidirectional chatbot solution that analyses user software requirements and provides viable suggestions to the user regarding their service. Previously, CORDULA chatbot was developed to analyze the software requirements but cannot keep the conversation’s context. The Rasa framework is integrated with the knowledge base to solve the issue, the knowledge base provides domain-specific knowledge to the chatbot. The software description is passed through the natural language understanding process to give consciousness to the chatbot. This process involves various machine learning models, including app family classification, to correctly identify the domain for user OTF service. The statistical models like naïve Bayes, kNN and SVM are compared with transformer models for this classification task. Furthermore, the entities (functional requirements) are also separated from the user description. The chatbot provides the suggestion of requirements from the preliminary service template with the support of the knowledge base. Furthermore, the generated response is compared with the state-of-the-art DialoGPT transformer model and ChatterBot conversational library. These models are trained over the software development related conversational dataset. All the responses are ranked using the DialoRPT model, and the BLEU score to evaluates the models’ responses. Moreover, the chatbot mod- els are tested with human participants, they used and scored the chatbot responses based on effectiveness, efficiency and satisfaction. The overall response accuracy is also measured by averaging the user approval over the generated responses.

Proactive Management of Requirement Changes in the Development of Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Preuß, Daniel (Applied Sciences)
Requirement changes and cascading effects of change propagation are major sources of inefficiencies in product development and increase the risk of project failure. Proactive change management of requirement changes yields the potential to handle such changes efficiently. A systematic approach is required for proactive change management to assess and reduce the risk of a requirement change with appropriate effort in industrial application. Within the paper at hand, a novel method for Proactive Management of Requirement Changes (ProMaRC) is presented. It is developed in close collaboration with industry experts and evaluated based on workshops, pilot users’ feedback, three industrial case studies from the automotive industry and five development projects from research. To limit the application effort, an automated approach for dependency analysis based on the machine learning technique BERT and semi-automated assessment of change likelihood and impact using a modified PageRank algorithm is developed. Applying the method, the risks of requirement changes are assessed systematically and reduced by means of proactive change measures. Evaluation shows high performance of dependency analysis and confirms the applicability and usefulness of the method. This contribution opens up the research space of proactive risk management for requirement changes which is currently almost unexploited. It enables more efficient product development.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Powder Spread Process Monitoring in Polymer Laser Sintering and its Influences on Part Properties - Klippstein, Sven Helge; Heiny, Florian; Pashikanti,, Nagaraju; Gessler, Monika; Schmid, Hans-Joachim (JOM - The Journal of The Minerals, Metals & Materials Society (TMS))
Confidence in additive manufacturing technologies is directly related to the predictability of part properties, which is influenced by several factors. To gain confidence, online process monitoring with dedicated and reliable feedback is desirable for every process. In this project, a powder bed monitoring system was developed as a retrofit solution for the EOS P3 laser sintering machines. A high-resolution camera records each layer, which is analyzed by a Region-Based Convolutional Neural Network (Mask R-CNN). Over 2500 images were annotated and classified to train the network in detecting defects in the powder bed at a very high level. Each defect is checked for intersection with exposure areas. To distinguish between acceptable imperfections and critical defects that lead to part rejection, the impact of these imperfections on part properties is investigated.

Fortschrittskontrolle der Modellierung mechatronischer Produkte - Gräßler, Iris; Wiechel, Dominik; Thiele, Henrik (Tagungsband der Fachtagung VDI-Mechatronik)
Die Anforderungen an die Entwicklung mechatronischer Systeme sind seit der Erstfassung der VDI Richtlinie 2206 im Jahr 2004 stetig gestiegen. Nach einer umfassenden Überarbeitung ist 2021 die Richtline im Weißdruck neu veröffentlicht worden. Neben dem Systemdenken als gestärktes Kernelement des V-Modells und sechs Kontrollpunkten nur Gliederung der sachlogischen Aufgaben ist die durchgängig explizite „Modellierung und Analyse“ eine wesentliche Neuerung der Richtlinie. Da sich die Kontrollfragen nur auf den Entwicklungsprozess im Ganzen beziehen, wird durch die Betrachtung der Modellierung eines Batteriesystems aus einem Entwicklungsprojekt eines deutschen Automobilherstellers die folgende Forschungsfrage betrachtet: Welche spezifischen Kontrollfragen zu Fortschritt und Reifegrad der Modellierung eines Batteriesystems können aus den Kontrollpunkten des V-Modells (VDI 2206:2020) gefolgert werden? Als Ergebnis der Forschung liegen hinsichtlich der Modellierung eines spezifischen Systems detaillierte Kontrollfragen vor, die eine methodische Unterstützung für die modellbasierte Systementwicklung komplexer mechatronischer Systeme bieten. Zusätzlich ermöglichen sie der Projektleitung die Überprüfung des aktuellen Status der Entwicklung und sichern die Vollständigkeit des Systemmodells ab.

Model-Based Effect-Chain Analysis for Complex Systems - Gräßler, Iris; Wiechel, Dominik; Koch, Anna-Sophie; Preuß, Daniel; Oleff, Christian (Proceedings of the Design Society)
Abstract Effect chain modeling approaches are applied to model cause-effect relations and analyze affected elements and dependencies. In this paper a systematic literature research is conducted to derive main characteristics and limitations of existing approaches. Then, the Model-based Effect Chain Analysis (MECA) method is introduced. Evaluation proves applicability of the method by means of a case example. This is done in the context of a project with a German automotive company. In the project 66 workshops were conducted to model certification-compliant effect chains in accordance to the UN ECE 156.

Einfluss der Berufserfahrung von Multiplikatorinnen und Multiplikatoren auf die Wirksamkeit von Fortbildungsmaßnahmen zur frühen mathematischen Bildung. Zeitschrift Für Erziehungswissenschaft - Hagena, Maike; Bruns, Julia; Gasteiger, Hedwig (Zeitschrift für Erziehungswissenschaft)
Teachers expect facilitators to have own teaching experience as a teacher in order to be able to carry out effective teacher professional development programs. As part of the project EmMa(M), it is investigated, to which extent the teaching experience of facilitators influences the development of early childhood teachers' (n = 83) mathematical pedagogical content knowledge (MPCK) and early childhood teachers' enjoyment of mathematics in the context of a teacher professional development program. It turns out that the teaching experience of the facilitators has no influence on the development of early childhood teachers' MPCK, but favors the development of early childhood teachers' enjoyment of mathematics. Controlling for this increased enjoyment an influence of teaching experience on the development of early childhood teachers' MPCK emerges, but in favor of the participating facilitators who have no teaching experience but have a university degree.
Keywords: Facilitator professional development; Early childhood teachers; Teaching; experience; Early mathematics education

Citizen Social Science in Germany—cooperation beyond invited and uninvited participation - Göbel, Claudia; Mauermeister, Sylvi; Henke, Justus (Humanities and Social Sciences Communications)
Abstract This article presents an overview of characteristics of Citizen Social Science (CSS) in Germany. CSS is defined as scientific research in the humanities and social sciences, carried out in cooperation between professional and non-professional researchers. The study draws on an online survey and semi-structured interviews with project coordinators and co-researchers. It finds that participatory research activities in the humanities and social sciences are very diverse in their disciplinary traditions and organisational settings. Key features of CSS activities initiated inside as well as outside academic institutions are analysed to understand patterns of participation and cooperation. The results show that CSS activities are frequently realised in heterogeneous consortia of academic and non-academic partners. These consortia influence interactions between professional and non-professional researchers. To investigate these observations further, the article extends the analytical gaze from participation of individual volunteers to various forms of cooperation in consortia. This shift in attention brings to sight additional actors and activities that are usually not, or only marginally, considered in discussions about C(S)S. Staff of civil society organisations, municipalities, schools or cross-sectoral initiatives as well as university students are involved in making CSS work. In addition to research tasks, CSS rests on science communication, project management and intermediation activities. This extended perspective captures more diverse constellations of knowledge production in participatory research in the social sciences and humanities than the common focus on participation. In this way, the article aims to lay the groundwork for understanding the functioning of CSS beyond aspects described by the concept of invited and uninvited participation. It shows that CSS activities are not limited to capacitating lay people for participation in science. A more adequate description is that such projects are concerned with facilitating cooperation with co-researchers and other partners in consortia inside and outside of academia. On this basis, the article introduces the notion of cooperation capacity as a heuristic device to propose new prompts for research on CSS as well as for supporting CSS practice.
Keywords: General Economics; Econometrics and Finance; General Psychology; General Social Sciences; General Arts and Humanities; General Business; Management and Accounting